From passive to active: Flexibility from electric vehicles in the context of transmission system development. (1st November 2020) - Gunkel, Philipp Andreas; Bergaentzlé, Claire; Græsted Jensen, Ida; Scheller, Fabian
Highlights: Modelling impacts of electric vehicle flexibility compared to grid expansion. Electric vehicle flexibility substitutes solar power with wind power. Marginal effect on stationary battery deployment through grid expansion. Local reduction of electricity price fluctuations by electric vehicle flexibility. Electricity price fluctuations are spatially smoothed by grid expansion. Abstract: Electrification of transport in RES-based power system will support the decarbonisation of the transport sector. However, due to the increase in energy demand and the large peak effects of charging, the passive integration of electric cars is likely to undermine sustainability efforts. This study investigates three different charging strategies for electric vehicle in Europe offering various degrees of flexibility: passive charging, smart charging and vehicle-to-grid, and puts this flexibility in perspective with the flexibility offered by interconnections. We use the Balmorel optimization tool to represent the short-term dispatch and long-term investment in the energy system and we contribute to the state-of-the-art in developing new methodologies to represent home charging and battery degradation. Our results show how each step of increased charging flexibility reduces system costs, affects energy mix, impacts spot prices and reduces CO2 emissions until the horizon 2050. We quantify how flexible charging and variable generation mutually support each other (>100 TWh from wind and solar energy in 2050) and restrict the business case for stationary batteries, whereas passive charging results in a substitution of wind by solar energy. The comparison of each charging scheme with and without interconnection expansion highlights the interplay between European countries in terms of electricity prices and CO2 emissions in the context of electrified transport. Although the best outcome is reached under the most flexible scenario at the EU level, the situation of the countries with the cheapest and most decarbonised electricity mix is damaged, which calls for adapted coordination policy at the EU level.